Dynamics and spectroscopy of molecular ensembles in a lossy microcavity - Ulusoy, Inga; Vendrell, Oriol (The journal of chemical physics, 2020)
The radiative and nonradiative relaxation dynamics of an ensemble of molecules in a microcavity are investigated with emphasis on the impact of the cavity lifetime on reactive and spectroscopic properties. Extending a previous study [I. S. Ulusoy et al., J. Phys. Chem. A 123, 8832-8844 (2019)], it is shown that the dynamics of the ensemble and of single molecules are influenced by the presence of a cavity resonance as long as the polariton splitting can be resolved spectroscopically, which critically depends on the lifetime of the system. Our simulations illustrate how the branching between nonradiative intersystem crossing and radiative decay through the cavity can be tuned by selecting specific cavity photon energies resonant at specific molecular geometries. In the case of cavity-photon energies that are not resonant at the Franck-Condon geometry of the molecules, it is demonstrated numerically and analytically that collective effects are limited to a handful of molecules in the ensemble.